Effect of Zinc on the Physical Properties of Tellurite Glass - Shaharuddin, Rosmawati; Abd. Aziz, Sidek; Talib, Zainal Abidin; Hussein, Mohd Zobir (Asian Network for Scientific Information, 2008)

(untitled)
A series of binary tellurite glass samples containing zinc oxide, ranging from 10 to 40 mol%, were successfully prepared. Longitudinal and shear ultrasonic wave velocities were measured at room temperature and were taken at 5 MHz. Elastic properties, Poison`s ratio, microhardness, Debye temperature and fractal bond connectivity have been calculated from the measured density and ultrasonic wave velocities. Results from the studies show that the densities of all glasses increase from 5098 to 5283 kg m-3, molar volumes decrease from 29.773 to 24.287 m3 mol-1 and the transition temperature, Tg decreases from 381.17 to 360.52°C with the substitution of TeO2 by ZnO content. Both the longitudinal and shear wave velocities decrease with increase of ZnO composition. The experimental results indicated that the elastic constants depend upon the composition of the glasses. The role of the ZnO inside the glass network is also discussed. Quantitative analysis based on bond compression model has been carried out, in order to obtain more information about the structure of these glasses.